Biopunk Dystopias - Schmeink, Lars (Liverpool University Press, 2016)
'Biopunk Dystopias' contends that we find ourselves at a historical nexus, defined by the rise of biology as the driving force of scientific progress, a strongly grown mainstream attention given to genetic engineering in the wake of the Human Genome Project (1990-2003), the changing sociological view of a liquid modern society, and shifting discourses on the posthuman, including a critical posthumanism that decenters the privileged subject of humanism. The book argues that this historical nexus produces a specific cultural formation in the form of
Includes bibliographical references (pages247-265) and index. - Description based on print version record
Keywords: Biotechnology in literature; Science fiction; Science fiction; 21st century; History and criticism; Fiction and related items; Biotechnologie dans la litterature; LITERARY CRITICISM; Science Fiction & Fantasy; BIOGRAPHY & AUTOBIOGRAPHY; Literary; Criticism; interpretation; etc